The Value of Jointly Held Conferences: Benefits and Considerations for Planners and Participants - Allison Nichols; Lisa Chase; Jason Gordon; Diana Rshash (Journal of Human Sciences and Extension, 2020)
University faculty and staff regularly participate in academic conferences as part of their professional responsibilities, yet the literature on their value is scarce, especially when examining conferences held jointly by two associations. Research is needed to help association leaders, planning committees, and attendees make informed decisions about conference organization and participation. This paper highlights the benefits and challenges of a jointly held academic conference for participants, association leaders, and organizational liaisons. In June of 2016, two Cooperative Extension associations, the National Association of Community Development Extension Professionals (NACDEP) and the Association of Natural Resource Extension Professionals (ANREP), jointly held a conference in Burlington, VT. Surveys were administered to conference participants, planning committee members, and liaisons at the United States Department of Agriculture National Institute of Food and Agriculture (NIFA) to collect data immediately following the conference and six months later. Using the Community Capitals Framework (CCF) to organize evaluation results, the authors discuss the benefits and challenges of planning, sponsoring, and attending the conference from the perspectives of these different groups. The authors focus on three community capitals: human capital, social capital, and cultural capital. Based on the findings, they offer recommendations for future evaluation of jointly held academic conferences.